A Stochastic Petri Net-Based Approach for Evaluating the Performability of Internet of Medical Things - Bezerra, Thiago; Callou, Gustavo; França, Cleunio; Tavares, Eduardo Antonio Guimaraes (Anais do Latin-American Symposium on Dependable Computing (LADC), 2024)
Internet of Things (IoT) allows components to be monitored remotely utilizing existing network infrastructures, facilitating the integration of diverse computing systems. IoT environments can interact with a wide array of devices and communication protocols, making them highly adaptable across multiple domains. By supporting diverse communication protocols, IoT environments ensure compatibility and interoperability among different devices and systems. This adaptability enables IoT solutions to be applied in numerous fields, including healthcare. For instance, hospitals have adopted the Internet of Medical Things (IoMT) to collect and transmit patient data to health professionals, as critical patients must be monitored uninterruptedly. Healthcare systems typically require high availability, in which connectivity is essential for critical medical decisions. This paper presents a modeling approach based on stochastic Petri nets (SPN) to evaluate the availability and performance of IoMT systems. The proposed technique focuses on the communication analysis between IoMT devices, which is illustrated through two case studies in the paper. The achieved results have shown that the availability was improved, reducing the downtime by over 93%. Moreover, the performance was improved by over 25%.